Synthesis, cytotoxic activity and quantum chemical calculations of new 7-thioxopyrazolo[1,5-f]pyrimidin-2-one derivatives - Kökbudak, Zülbiye; Saracoglu, Murat; Akkoç, Senem; Çimen, Zeynep; Yilmazer, M. Izzettin; Kandemirli, Fatma (Elsevier BV, 2020)
Abstract The reactions of 1-amino-2-thioxo-1,2-dihydropyrimidin derivatives 1 and 2 with chloroacetyl chloride in the presence of sodium acetate led to the formation of 7-thioxopyrazolo [1,5-f]pyrimidin-2(1H,3H,7H)-one derivatives (3 and 4) in 78–80% yields. The structure of these newly synthesized compounds 3 and 4 were fully characterized by 1H NMR, 13C NMR, FT-IR spectroscopies and elemental analyses. The quantum-chemical calculations were made to find molecular properties of the 3 and 4 by using DFT/B3LYP method with 6–311++G(2d, 2p) basis set. Quantum chemical features such as HOMO, LUMO, energy gap, ionization potential, chemical hardness, softness, electronegativity, dipole moment and etc. values for gas and solvent phase of neutral molecules were calculated and discussed. Furthermore, the cytotoxic activities of 3 and 4 were tested against human liver cancerous cell line (HepG2) and human breast cancerous cell line (MDA-MB-231) for 24 h and 48 h, respectively.
Keywords: 3. Good health